Discharge before noon: An achievable hospital goal. Issue 4 (20th January 2014) - Wertheimer, Benjamin; Jacobs, Ramon E. A.; Bailey, Martha; Holstein, Sandy; Chatfield, Steven; Ohta, Brenda; Horrocks, Amy; Hochman, Katherine
<x xml:space="preserve">Abstract</x> BACKGROUND Late afternoon hospital discharges are thought to contribute to admission bottlenecks, overcrowding, and increased length of stay (LOS). In January 2012, the discharge before noon (DBN) percentage on 2 medical units was 7%, below the organizational goal of 30%. OBJECTIVE To sustainably achieve a DBN rate of 30% and to evaluate the effect of this intervention on observed‐to‐expected (O/E) LOS and 30‐day readmission rate. DESIGN Pre‐/post‐intervention retrospective analysis. SETTING Two acute care inpatient medical units in an urban, academic medical center. PATIENTS All inpatients discharged from the units. INTERVENTION All staff helped create a checklist of daily responsibilities at a DBN kickoff event. We initiated afternoon interdisciplinary rounds to identify next‐day DBNs and created a website for enhanced communication. We provided daily feedback on the DBN percentage, rewards for success, and real‐time opportunities for case review. MEASUREMENTS Calendar month DBN percentage, O/E LOS, and 30‐day readmission rate. RESULTS The DBN percentage increased from 11% in the 8‐month baseline period to an average of 38% over the 13‐month intervention (P = 0.0002). The average discharge time moved 1 hour and 31 minutes earlier in the day. The O/E LOS declined from 1.06 to 0.96 (P = 0.0001), and the 30‐day readmission rate declined from 14.3% to 13.1% (P = 0.1902). CONCLUSIONS Our study demonstrates that increased DBN is an achievable and sustainable goal for hospitals. Future work will allow for better understanding of the full effects of such an intervention on patient outcomes and hospital metrics. Journal of Hospital Medicine 2014;9:210–214. © 2014 Society of Hospital Medicine